THE INFLUENCE OF TAX MORALS, GOOD GOVERNMENT GOVERNANCE, AND SOCIAL MEDIA ON INDIVIDUAL TAXPAYER COMPLIANCE WITH TRUST AS MODERATION - Ramashar, Wira; Fitriana, Nur; S Harahap, Putrri Dasti (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to analyze the influence of tax morality, good government governance, and social media on the compliance of individual taxpayers with trust as a moderation variable. The background of the research departs from the phenomenon of low compliance of individual taxpayers in Indonesia, especially in the city of Pekanbaru, even though the government has made various efforts to socialize and digitize tax services. This study uses a quantitative approach with a survey method through a questionnaire distributed to individual taxpayers domiciled in the city of Pekanbaru. The sampling technique was determined using the lemeshow formula with a sample number of 100 samples. The collected data was analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method to test the relationships between variables. The results of the study are expected to show that tax morality, good government governance, and social media have a positive effect on taxpayer compliance, and trust is able to strengthen these relationships. This research provides a theoretical contribution by expanding the application of the Theory of Planned Behavior (TPB) in the context of tax compliance, as well as providing practical implications for the Directorate General of Taxes in improving socialization strategies and strengthening taxpayers' trust in tax authorities